Reducción de costos asociados a los desperdicios de un producto perteneciente a una empresa manufacturera (Reducing costs associated with waste from a product of a manufacturing company) - Martínez Quezadas, Miguel; Garza Villegas, Juan Baldemar (Facultad de Contaduría Pública y Administración U.A.N.L., 2013)
Abstract. This project is diagnosed two causes root (autonomous maintenance deficient system and there is no system for receiving raw material) that encourage production defects of a certain product. Having implemented the solutions which were: the redesign of autonomous maintenance system and created a system for receiving raw material, one could see a reduction of 73% for defects with respect to the previous year.